2021
DOI: 10.1186/s40634-021-00422-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of posterior capsular release for flexion contracture in posterior-stabilized total knee arthroplasty

Abstract: Purpose Posterior capsular contracture causes stiffness during knee extension in knee osteoarthritis. Furthermore, in posterior-stabilized total knee arthroplasty (PS-TKA), a unique design such as the cam mechanism could conflict with the posterior capsule (PC) causing flexion contracture (FC). However, few studies have focused on the anatomical aspects of the PC. This study aimed to investigate the anatomical site and forms of posterior capsular attachment to the femoral cortex, and to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Kinoshita et al. [ 14 ] performed a cadaveric study identifying attachment sites of the posterior capsule using computed tomography scan. They performed a stepwise release and found the gastrocnemius tendon and posterior capsule were integrally attached to the femoral cortex at the medial and lateral condyles, whereas the posterior capsule at the intercondylar fossa was independently attached directly to the femoral cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinoshita et al. [ 14 ] performed a cadaveric study identifying attachment sites of the posterior capsule using computed tomography scan. They performed a stepwise release and found the gastrocnemius tendon and posterior capsule were integrally attached to the femoral cortex at the medial and lateral condyles, whereas the posterior capsule at the intercondylar fossa was independently attached directly to the femoral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical methods to correct preoperative flexion contracture have been described including intraoperative manipulation, removal of posterior condylar osteophytes and loose bodies, posterior capsular release, posterior cruciate ligament release, decrease of posterior condylar offset, and additional resection of the distal femur [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. No consensus has emerged on the optimal technique to restore full extension [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of posterior capsular release on component gaps at 0° and 90° have been analysed in cadaveric knees [2]. In a cadaveric study, Kinoshita et al demonstrated that there are measurable effect differences in knee extension angles when the posterior capsule is released at each of three parts of the distal femur in a stepwise manner starting with release at the intercondylar notch followed by medial and then lateral release [7]. In line with previous reports, our study found that posterior capsular release from the medial side to and including the intercondylar notch increased the component gap sufficiently at extension without component gap change at mid to deep flexion in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Mid‐flexion instability leads to increased polyethylene wear and causes a subjective feeling of instability when walking on sloped surfaces or when descending stairs [3, 5, 9]. Posterior capsular release across the full medio‐lateral width of the distal femur (hereafter referred to as full PCR) has been found to increase the component gap at extension without an increase in the component gap at flexion and provided successful outcomes on controlling gap mismatch [2, 7]. However, this procedure theoretically carries an inherent risk of injury to the important neurovascular structures contained in the popliteal fossa [20].…”
Section: Introductionmentioning
confidence: 99%
“…Knees and elbows have been shown to be the most vulnerable joints to PJTS. A flexion contracture model was chosen to mimic PJTS in the knee, the most debilitating and clinically relevant form [ 17 , 28 ]. In particular, in a flexion contracture, the posterior capsule has proven to be at the heart of this condition with its densely packed connective tissue, whereas its anterior counterpart remains largely unaffected [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%